Evaluation of Antioxidant Activity, Antimicrobial and Fungicidal Effect of Organic Extracts of Cork Oak Acorns Infested by Carpophagous Insects - Adjami, Y.; Ouakid, M. L.; Saouli, A.; Bensafi, H.; Soltani, N.; Hayouni, E. A.; Everarts, C. (INTERNATIONAL SYMPOSIUM ON MEDICINAL AND AROMATIC PLANTS - SIPAM2009, 2010)
The Algerian cork oak forest is constituted with numerous essences(Quercus faginea, Quercus coccifera, Quercus suber). This last one establishes an essential element of the physical, climatic and especially socioeconomic balance of the populations of the rural zones and the country in general. An appeal to the regeneration would be indispensable for the rehabilitation of these forests, where from the importance of acorns, which play a major role in the regeneration of this essence. The purpose of this work is to estimate antioxidant activity, antimicrobial and fungicidal effect of the essential oil of organic extracts of the cork oak acorns attacked with the procession of insects called Carpophagous Insects. We extracted acorns of cork oak infested with insects by using organic solvents as the acetone, the chloroform, the ethanol and also extract of water. We measured at first the total lipids according to Goldsworthy's method (1972). The antioxidant activity of samples was determined by two methods, the one based on the discoloration of a solution of cation ABTSo +. The original product, ABTS is going to generate cations ABTSo + which are free radicals and the other one based on the discoloration of a solution of beta-carotene (beta-carotene bleaching method). Extracts, obtained were individually estimated against some phytopathogenes: Penicillium digitalum, Penicillium italicum, Botrytis fabae, Botrytis cinera, Ascophyta fabae, Fusarium oxysporum, as well as against pathogenic microorganisms such as Geotrichum candidum, Aspergillus, Candida galbrata, Candida albicans, and Saccharomyces cerevisiae. Extracts were so individually estimated against a sample group of 4 bacteria including: Pseudomonas aeruginosa ATCC 9027, Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29212 and Escherichia coli ATCC 25922. Results show that all the extracts stemming from attacked acorns contain less lipids than the extracts of the healthy acorns. These same extracts present an antioxidant activity, a significant antimicrobial and fungicidal effect. This biologic activity is a function of various used solvents.
The following values have no corresponding Zotero field: periodical: INTERNATIONAL SYMPOSIUM ON MEDICINAL AND AROMATIC PLANTS - SIPAM2009 pub-location: PO BOX 500, 3001 LEUVEN 1, BELGIUM
Keywords: acorns; antimicrobial and fungicidal effect; antio